Tindak Tutur Kebencian dalam Status Whatsapp - Yunita Suryani; Rika Istianingrum; Idhoofiyatul Fatin (SUAR BETANG, 2022)
Hate speech acts on social media often become criminal law complaints offenses with the aim of obtaining justice. This study uses a qualitative descriptive method that aims to describe hate speech acts on Whatsapp status. The research data comes from the screenshot of the Whatsapp status obtained by the researcher from BAP (News of the Judiciary), the researcher as a linguist witness. The data presented in the BAP according to the chronology or context of the event were analyzed using Searle's speech acts. Based on the analysis, the writer found several kinds of hate speech acts, namely (1) insulting expressive and warning directives; (2) derogatory expressive and directive (giving warning); (3) expressive accusing and assertive (giving statements); (4) assertive accusing, assertive inciting, expressive insulting, and threatening commissive; (5) commissive, challenging, and expressive insulting; (6) expressive contempt and assertive accusing; (7) derogatory expressiveness; (8) assertive accusing, expressive insulting; (9) commissive threats; (10) expressive insulting, assertive admitting, and assertive accusing.AbstrakTindak tutur kebencian dalam media sosial sering menjadi delik aduan hukum pidana dengan tujuan memperoleh keadilan. Penelitian ini menggunakan metode deskriptif kualitatif dan bertujuan mendeskripsikan tindak tutur kebencian dalam status Whatsapp. Data penelitian berasal dari tangkapan layar status Whatsapp yang diperoleh peneliti dari BAP (Berita Acara Peradilan) peneliti sebagai ahli bahasa. Data yang disajikan dalam BAP sesuai dengan kronologi atau konteks peristiwa dan dianalisis menggunakan teori tindak tutur Searle (1975). Hasil penelitian menunjukkan bahwa ada beberapa tindak tutur kebencian, yaitu (1) ekspresif menghina dan direktif memberi peringatan; (2) ekspresif menghina dan direktif (memberi peringatan); (3) ekspresif menuduh dan asertif (memberikan pernyataan); (4) asertif menuduh, asertif menghasut, ekspresif menghina, dan komisif mengancam; (5) komisif, menantang, dan ekspresif menghina; (6) ekspresif menghina dan asertif menuduh; (7) ekspresif menghina; (8) asertif menuduh, ekspresif menghina; (9) komisif mengancam; (10) ekspresif menghina, asertif mengakui, dan asertif menuduh.